Pengembangan Media Pembelajaran Interaktif Capinus Air Pelajaran IPA Pokok Bahasan Siklus Air - Defantari, Evy Lissa; Yulianto, Sigit (Jurnal Penelitian Pendidikan IPA, 2024)
Researcher observations were carried out at SD Negeri Beringin 02, which showed that there were problems related to science education content, including limited learning media and low student learning outcomes. The researcher aims to develop, and test the feasibility and test effectiveness of the Capinus Air learning media, namely Canva-based learning media for science lesson content, with the hope of improving the learning outcomes of class V students at SD Negeri Beringin 02, Central Java, especially in the science subject Water Cycle (Hydrology). ). Using the Borg and Gall model with modifications to the 8 stages of the development model, namely: potential and problems; data collection; product design; design validation; design revision; trial product; product revision; and trial use. In Class V, 22 students took part in large-scale experiments and 6 students carried out small-scale experiments and collected data through questionnaires, interviews, and documentation. The t-test results determine a significance value of 0.00 on both small and large scales. For the N-Gain value criteria, it is included in the "High" category, the calculation produces 0.78 on a small scale and a large scale, namely 0.77. Therefore, Capinus Air Interactive learning media is very suitable for teaching science and improving student learning outcomes.